Energy System Management for Substation of Electricity Generating Authority of Thailand base on Artificial Neural Network: การจัดการพลังงานสำหรับสถานีไฟฟ้าย่อยของการไฟฟ้าฝ่ายผลิตแห่งประเทศไทย บนพื้นฐานของโครงข่ายประสาทเทียม - LUECHAI, SIRAPHONG (Srinakharinwirot University Engineering Journal, 2020)
The Irregular and unstable Electrical Power Problems solving of Power Station with Artificial Neural Network Technique aims make the voltage value to stable and to create the mathematics model. From the comparison result found that the obtainable electrical value of the artificial neural network method with the initial electrical value. The standard deviation has decreased from 2.4503 to 0.7559 , representing 69.15% and the variance has decreased from 6.0041 to 0.5714 , representing 90.48%. Therefore, the artificial neural network method has increased voltage stability.